Strong Diffusion Suppression of Low Energy–Implanted Phosphorous in Germanium by N2 Co-Implantation. (1st January 2015) - Thomidis, C.; Barozzi, M.; Bersani, M.; Ioannou-Sougleridis, V.; Vouroutzis, N. Z.; Colombeau, B.; Skarlatos, D.
Abstract : In this work an effective diffusion suppression of low energy – high dose (11 keV/10 15 cm −2 ) phosphorous in 10 keV/5 × 10 14 cm − 2 N2 + -implanted p-germanium is demonstrated. Diffusion of both species after isochronal 30 sec RTA annealing at 550–650°C has been studied by SIMS in the presence of Al2 O3 as surface capping layer. Nitrogen shows anomalous non-Fickian diffusion towards the Al2 O3 /Ge interface, while phosphorous dose loss and diffusion to the bulk are strongly suppressed in comparison to Ge substrate without nitrogen implantation. Possible physical mechanisms (involving phosphorous-vacancies or phosphorous-nitrogen complexes, and end-of-range interstitials) that explain this result are presented and discussed.